A cognitive function test utilizing eye-tracking technology in virtual reality is useful to distinguish between normal cognition, MCI and mild dementia - Katsuyoshi Mizukami; Masatomo Taguchi; Takashi Kouketsu; Naoki Sato; Yoshiro Tanaka; Masahiko Iwakiri; Yoichiro Nishina; Yuan Ma; Iakov Chernyak; Shintaro Karaki (Archives of Gerontology and Geriatrics Plus)
Aim: This study aimed to verify the usability of our newly developed virtual reality-based cognitive function examination (VR-E) to differentiate mild cognitive impairment (MCI) from normal cognition and mild dementia. Method: The subjects of analysis were 71 people (26 males and 45 females, aged from 59 to 94), including 31 with normal cognitive function, 26 with MCI, and 14 with mild dementia, according to the Clinical Dementia Rating (CDR). The total score and each cognitive domain (memory, judgement, spatial cognition, calculation, language function) score of VR-E were compared among CDR0, CDR0.5 and CDR1. In addition, for CDR0 vs. CDR0.5 and CDR 0.5 vs. 1, the areas under the curve (ROC) were examined using the total score and each cognitive domain of VR-E. Results: There were significant differences between the three CDR groups in the VR-E scores as well as each VR-E cognitive domain score. The ROC analysis with an AUC value for the VR-E scores between CDR 0 and 0.5 was 0.71, and between CDR 0.5 and 1 was 0.92. For each VR-E cognitive domain, the ROC analysis with an AUC value between CDR 0 and 0.5 was 0.63 for memory, 0.79 for judgment, 0.70 for spatial cognition, 0.62 for calculation, and 0.57 for language. Between CDR 0.5 and 1, the AUC values were 0.81 for memory, 0.75 for judgment, 0.82 for spatial cognition, 0.88 for calculation, and 0.86 for language. Conclusion: The results suggest that VR-E is useful for differentiating mild cognitive impairment from normal cognition and early dementia.